KARAKTERISTIK YOGURT YANG TERBUAT DARI BERBAGAI JENIS SUSU DENGAN PENAMBAHAN KULTUR CAMPURAN Lactobacillus bulgaricus DAN Streptococcus thermophillus - Fatmawati, Umi; Prasetyo, Faisal I.; T.A, Mega Supia; Utami, Ardiyanti Nur (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2013)
ABSTRACT-Yoghurt is one of fermented milk product with the addition of lactic acid microbes such as Lactobacillus bulgaricus and Streptococcusthermophillus. The aim of this experiment is determining the characteristics of yogurt made from five different dairy ingredients, each of them are added with a mixture of bacteria Lactobacillus bulgaricus and Streptococcusthermophillus. The dairy ingredients used are: fresh cow's milk, skim milk, UHT milk, soy bean milk, and goat's milk. Starter was given with mixing two species of lactic acid bacteria with the ratio 1:1 and the provision of starter concentration is 5% (v / v). The parameters’ have been observed for lactic acid levels, pH and total number of microbes carried out during 14 days of storage. To examine the effect of different kinds of milk and storage time toward the changes in lactic acid level, pH and total number of microbes, we analyzed with ANAVA by two factorial test and if there are any significant effect, it followed by DMRT test. The results obtained from yogurt product quality were yoghurt made from UHT milk was the best quality because it has the lowest average pH of 4,67, the highest lactic acid content of 1,2 % and most stable total microbial 3,05 x108 cells / ml during the preservation time.